Wide-Scale Continuous Quality Improvement: A Study of Stakeholders' Use of Quality of Care Reports at Various System Levels, and Factors Mediating Use - Laycock, Alison F.; Bailie, Jodie; Percival, Nikki A.; Matthews, Veronica; Cunningham, Frances C.; Harvey, Gillian; Copley, Kerry; Patel, Louise; Bailie, Ross (Frontiers in Public Health, 2019)
Introduction: Increasing the use of evidence in healthcare policy and practice requires greater understanding of how stakeholders use evidence to inform policy, refine systems and change practice. Drawing on implementation theory, we have used system-focused participatory research to engage diverse stakeholders in using aggregated continuous quality improvement (CQI) data from Australian Indigenous primary health care settings to identify priority evidence-practice gaps, barriers/enablers and strategies for improvement. This article reports stakeholders’ use or intended use of evidence at various levels of the system, and factors mediating use. Material and methods: Interviews were undertaken with a purposeful sample of 30 healthcare stakeholders in different roles, organisation types and settings in one Australian jurisdiction and with national participants, as part of the project’s developmental evaluation. Qualitative data were analysed to identify themes and categories relating to use of evidence. Results: Context-specific aggregated CQI data that were relatable to the diverse professional roles and practices provided an effective starting point for sharing perspectives, generating practice-based evidence and mobilising evidence-use. Interviewees perceived the co-produced findings as applicable at different levels and useful for planning, policy development, supporting best practice and reflection, capacity strengthening and developing new research. Factors mediating use were commitment to best practice; the credibility of the evidence and its perceived relevance to work roles, contexts and decision needs; report format and language; facilitation and communication; competing work pressures and the organisational environment for change. Conclusions: This study found that primary health care stakeholders used evidence on quality of care for a variety of purposes. This could be linked to the interactive research processes used to engage stakeholders in different roles and settings in interpreting data, sharing and generating knowledge. Findings indicate that system-based participatory research using CQI data and iterative, interactive and systematic CQI-based methods can be applied at scale to support concurrent action for healthcare improvement at different system levels. Factors known to influence implementation should be addressed within the research design to optimise evidence use. Further research is needed to explore the utility of interactive dissemination for engaging healthcare stakeholders in informing policy and system change.